ANALISIS PENERAPAN SISTEM KLASIFIKASI ISLAM DALAM PENGOLAHAN BAHAN PUSTAKA DI PERPUSTAKAAN PONDOK PESANTREN ASSALAM - Amanda, Dina Yulia (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2024)
The library is an organization that provides services in the form of information providers for all people who really need information, in this case, namely the users. This research is a qualitative research, there are also data sources in this study, namely primary data sources consisting of librarians, and secondary data sources obtained from references, both in the form of journals, articles, and various relevant research results. The research instrument used guidelines, namely interviews, while data collection methods used observation and interviews. The data processing and analysis techniques go through several stages, namely, data collection, data presentation, and drawing conclusions. And the results of the study show that the application of the Islamic DDC classification system used in the ASSALAM Islamic Boarding School library is a printed DDC Islamic summary classification system.